The Impact of Housing Loan/Financing on Malaysian Bank Risk Performances - Isa, Mohamad Yazid; Ishak, Muhammad Arif Fadilah; Abd Aziz, Noriza; Tapa, Afiruddin (Academic Research Publishing Group, 2018)
This study investigates the impact of housing loan/financing on bank risk performances in Malaysia. The data is collected from 12 commercial banks and 12 Islamic banks in Malaysia within the period of 2002-2016. Nonperforming loan (NPL) and loan loss provision (LLP) are used as proxies for bank risk and they are regressed with housing loan/financing, expenses, total loan, income, gross domestic product and inflation. The results from Random and Fixed Effect models show that housing loan/financing has significant impact on the NPL and the LLP of commercial banks and Islamic banks. The results also show that even though commercial banks seem to dominate housing loan/financing market, but Islamic banks are capable to compete with commercial bank in this specific type of financing